2022
DOI: 10.11648/j.jenr.20221101.11
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Agroforestry in Sustainable Fuelwood Supply in Kenya

Abstract: Sub Saharan African (SSA) region rely heavily on fuelwood for their energy needs and will potentially increase in the foreseeable future due to increased population growth in the region. The continued utilization of fuelwood in the region subject to inefficient technology of energy conversion is projected to put more increasing pressure on forest cover and resources. The decline in forest resources is a precursor to exploration of other resources that may provide energy to human, in which agroforestry comes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…The results also showed that sampled households who agreed that planting trees provides fuelwood and furniture wood (i.e., positive attitude) had a greater likelihood of adopting the agroforestry practices, ceteris paribus. Households using firewood as an energy source tend to plant more trees on their farmland than those using electricity, paraffin, and gas [29,55]. Moreover, tree species such as teak provide the raw material for furniture.…”
Section: Discussionmentioning
confidence: 99%
“…The results also showed that sampled households who agreed that planting trees provides fuelwood and furniture wood (i.e., positive attitude) had a greater likelihood of adopting the agroforestry practices, ceteris paribus. Households using firewood as an energy source tend to plant more trees on their farmland than those using electricity, paraffin, and gas [29,55]. Moreover, tree species such as teak provide the raw material for furniture.…”
Section: Discussionmentioning
confidence: 99%